Furthering democracy through the European Union's development policy: Legal limitations and possibilities - Morten Broberg (Danish Institute for International Studies (DIIS), 2010)
This working paper provides an analysis of the efforts by the European Union to support democracy building in developing countries. It focuses on the specific question of the legal obligations of, and limits for, the European Union in seeking to further democracy through its policies directed at developing countries. The core of the paper is an examination of the legal framework governing the Union's relations with developing countries and the possibilities for furthering democracy. The paper considers the European Union's determination of whether a third country complies, in legal terms, with its 'democratic obligations', and how it is able to control and sanction non-compliance. On the basis of these examinations the possibilities of furthering democracy and the rule of law in the Union's development cooperation legislation are analysed.
Keywords: 330; Entwicklungspolitik; Demokratisierung; Entwicklungshilfekonditionen; Entwicklungskooperation; EU-Staaten